Government Policy Effect Towards Energy-Efficient Appliances Purchase Intention In West Java - Zahra, Fathimatuz; Astuti, Yuhana (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
As the fourth most populous country in the world, Indonesia has a high population density, which contributes to greenhouse gas emissions, particularly through energy consumption. The household sector accounts for the highest energy consumption in Indonesia. To address these emissions, the government has established five main principles to achieve Net Zero Emission: increasing the benefits of household electricity and introducing an official label, the Energy Saving Mark Label, to designate products that meet the government's energy efficiency requirements. This study focuses on the purchasing behavior of residents in West Java regarding energy-efficient products, such as air conditioners, rice cookers, refrigerators, fans, and LED lamps, which are the main priorities of the government. The findings reveal that sub-variables of Government Policy, namely Price Factors, Economic Benefits, and Environmental Awareness, significantly influence Purchase Intention. However, other sub-variables, such as Policy and Propaganda, Social Interaction, Past Purchase Experience, Product Cognition, Gender, Age, Education, and Income, do not have a significant effect on Purchase Intention